Tinjauan Yuridis Putusan Pengadilan Tentang Perubahan dan Penambahan Nama dalam Catatan Sipil : Studi Putusan Nomor : 82/Pdt.P/2024/PN Arm - Marven A. Kasenda; Sherina Darius; Sarli S. Landota; Jeshica S. Toding; Siti Mutiara Ambo Upe; Winda Winda; Asri Susanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the legal consequences of changing and adding a person's name and to find out the procedure for changing and adding a person's name based on court decision number 82/Pdt.P/2024/PN Arm. The method used in this study is to use normative legal research. The results of the following study are that the legal consequences of changing a name or adding a name will affect the legal aspects of this civil registration, namely to ensure maximum legal certainty regarding personal events that occur in a person's life. Furthermore, a name change is made based on a decision from the district court that handles the application. In addition, people who change their names are required to register the name change with the Civil Registry Service which issues the Civil Registry deed within a maximum of 30 days after receiving a copy of the district court decision. The Civil Registry Service will then record the change next to the Civil Registry deed register and will also make a Civil Registry deed extract.